2013
DOI: 10.7763/ijcea.2013.v4.293
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Bioactive Compounds from Mango Peels Using Green Technology

Abstract: Abstract-Mango peels, wastes generated from fruit can processing, are a good source of functional ingredients such as phenolic compounds that has potential antioxidant properties. This study investigated the extraction of phenolic compounds from mango peels using subcritical water extraction (SCW). Experiments were performed in a batch laboratory-built equipment (50 ml volume of vessel) immersed in oil bath and temperatures ranging from 160 to 220 °C, extraction time of 30 to 120 min., material particle sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 13 publications
5
35
1
Order By: Relevance
“…The total phenolic content of the peel of freshly harvested mango fruit was found to be 11.90 mg GAE/g. This result was similar to the result (11.68 mg GAE/g) obtained by Tunchaiyaphum et al (2013). The value obtained in this present study was higher than the previous values reported for different varieties of mango peels; 45.25 -87.67 mg GAE/100g (Imran et al, 2013;Ramirez, Zambrano, Sepulveda, & Simirgiotis, 2014) and 0.86 g GAE/100g (De Almeida Monaco et al, 2014).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The total phenolic content of the peel of freshly harvested mango fruit was found to be 11.90 mg GAE/g. This result was similar to the result (11.68 mg GAE/g) obtained by Tunchaiyaphum et al (2013). The value obtained in this present study was higher than the previous values reported for different varieties of mango peels; 45.25 -87.67 mg GAE/100g (Imran et al, 2013;Ramirez, Zambrano, Sepulveda, & Simirgiotis, 2014) and 0.86 g GAE/100g (De Almeida Monaco et al, 2014).…”
Section: Resultscontrasting
confidence: 53%
“…To our knowledge, there has been no previous study to directly compare phenolics, vitamin C and antioxidant properties of mango peel, with respect to storage of mango fruit. However, phenolics and antioxidant properties of mango peel has been previously evaluated (Ajila et al, 2007;Kim, Brecht, & Talcott, 2007;Tunchaiyaphum, Eshtiaghi, & Yoswathana, 2013;De Almeida Monaco, Costa, Uliana, & Lima, 2014). The present study was designed to evaluate the bioactive components, antioxidant properties and inhibition of Fe 2+ -induced lipid peroxidation of mango peel as affected by storage of mango fruit at room and refrigeration temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…SCW is the most promising engineering approach that offers an environmentally friendly technique for extracting various compounds from plants and algae (Zakaria and Kamal 2016). Tunchaiyaphum et al (2013) extracted phenolic compounds from mango peels using SCW. The amount of phenolic compounds from mango peels using SCW extraction was higher than that using Soxhlet extraction technique.…”
Section: Subcritical Water Extractionmentioning
confidence: 99%
“…Polyphenol rich fractions of peel extract could be used as natural antioxidants and functional food or feed supplements (Berardini et al 2005). In a recent study, phenolic compounds from mango peels were successfully extracted using subcritical water (SCW) and this solvent is considered to be environmentally friendly for extraction of bioactive compounds (Tunchaiyaphum et al 2013). The subcritical water extraction is considered to be timesaving, results in high yield and no toxic solvent residues yielding method and therefore can be applicable for the food industry.…”
Section: Phenolic Antioxidantsmentioning
confidence: 99%